A newborn with three cochlear turns: Case report and literature review. (26th August 2015) - Hildrew, Douglas M.; Ananth, Ashwin; Rodriguez, Kimsey H.
Abstract : Objectives/Hypothesis: The human cochlea is most commonly considered to have two and a half turns. Although the causes of cochlear hypoplasia are well described, cochlear hyperplasia is a rarer entity that is poorly understood. We describe rare anatomic cochlear malformations identified in a 4‐month‐old male originally referred for evaluation after a failed newborn hearing screening. The full diagnostic evaluation, imaging findings, treatment, and follow‐up are described in detail. Cochleae with three turns are an uncommon malformation that is not included in current classifications schemes and may represent a distinct type of anomaly not caused by developmental arrest. Laryngoscope, 126:469–471, 2016